ERGONOMICS AND FUNCTIONAL REQUIREMENT IN THE DESIGN OF STUDENTS’ FURNITURE IN MOSHOOD ABIOLA POLYTECHNIC ABEOKUTA NIGERIA - ADEKUNLE IBRAHIM MUSA-OLOKUTA (Journal of Engineering Studies and Research)
A total of five hundred and fifty students were randomly selected in three schools of engineering; communication; science and technology. The existing furniture dimensions were measured. The maximum and minimum table height was determined. The results showed seat heights as compared with the students body sizes are expected to be in the range of 33.85 cm and 36.54 cm. Table height is expected to be in the range of 61.08 cm and 64.48 cm. The study concluded that data on the anthropometric dimension of students are provided and this could be used as database for the planning of future furniture in the lecture rooms.